High Performance Liquid Chromatography in Quantitative Assessment of Diosaginine Metabolic Output Isolated from Callus Cultures, Cellular Pendants and Root Poems in Medical Plant Ring - Mzahim Al Malla; Luma Al-Zonbaidi (College of Education for Pure Sciences, 2007)
ABSTRACT Callus cultures were obtained from stem and leaf segments of Trigonella foenum-graecum grown on Murashige and Skoog (MS) medium supplemented with combinations of Benzyl adenine (BA), Naphthaleneacetic acid (NAA). Maximum callusing 97% were obtained from stem segments grown on MS medium supplemented with a mixture of NAA 1.0 mg L-1 and BA 2.0 mg L-1. The friable callus was reasonable for cell suspension cultures. Liquid MS and B5 media with addition of NAA, BA, 2,4-D and Kinetin were used for induction of these cultures. Maximum and steadily growth of these suspensions were found on liquid B5 medium supplemented with 2,4-D (0.2 mg L-1) and Kin. (1.5 mg L-1 ) with leaf callus. The study established also a culture of hairy roots developed from those adventitious roots induced on intact fenugreek seedlings inoculated by Agrobacterium rhizogenes R1601. High performance liquid chromatography analysis confirmed the presence of diosgenin in callus at ratio 46.3%, In liquid medium of cell suspension derived from leaf callus at ratio of 50.2%, that of stem callus 24.1% . The ratio was at 21.79% of hairy root culture.